Leveraging Integrated Bike-Sharing with Existing Bus Rapid Transit (BRT) to Reduce Motor Vehicle in Central Jakarta Municipal - Daniella Daniella; Achmad Amri Dharma Wangsa (Department of Urban and Regional Planning, Diponegoro University, 2019)
Jakarta is one of the most congested cities in the world due to a plethora of motor vehicles used in the city. One of the government actions to address the issue is by implementing Bus Rapid Transit (BRT) as an alternative public transportation mode. However, according to the convenience walking distance standard, the BRT coverage the inhabitant to choose motor vehicle rather than walking. This paper purposes Bike-Sharing as the smart transportation mode to overcome such issue and predict the three potential places to establish sharing-bike stations according to the convenience walking distance standard. In this paper the walking distance is classified into 100 mater range (300 meter, 400 meter and 500 meter) projected using the euclidean distance principle. As the result for 300 meter standard, there are 809 potential bike-sharing stations consist of 164 main stations and 645 feeder stations, while the 400 meter standard needs 541 potential stations with 140 stations serve the BRT station directly and 401 stations as the feeder. Furthemore, with 500 meter standard, 359 stations consist of 131 main stations and 228 feeder stations is needed.